Kajian Dari Senyawa Umbi Bawang Putih (Allium sativum L.) terhadap Interaksi Aktif sebagai Analgetik-Antiinflamasi Secara in Silico - Monikasari, Hesti; Mardianingrum, Richa; Bachtiar, Kamiel Roesman (Jurnal Farmasi Sandi Karsa, 2023)
Pain is a form of emotional sensory discomfort associated with risk or damage to body tissues, this can arise when tissues are being damaged. The classification of pain is generally divided into two, namely acute pain and chronic pain. The treatment often used for acute pain (analgetic-anti-inflammatory) is ibuprofen. However, ibuprofen if consumed in the long term can cause some side effects for the body. The purpose of this study was to find candidates for medicinal ingredients from 96 compounds found in garlic bulbs (Allium sativum L.) as analgetic-anti-inflammatory. This research method uses experimental methods in silico which include molecular docking and molecular dynamics. The results of this study show that UBP20 compounds (tetracycline) have better toxicity than ibuprofen, as well as produce interactions that can be stabilized by the amino acids ARG120 and TYR355. Based on molecular dynamic results, UBP20 compounds have RMSD values of ±2.32 Å and ∆GTOTAL values of -24.27 kcal / mol. While Ibuprofen has an RMSD value of ±2.46 Å and ∆GTOTAL -35.21 kcal / mol. So it can be concluded that UBPP20 compounds have stable interactions with 1EQG receptors that can be used as candidates for analgetic-anti-inflammatory drugs, but do not yet have a lower ∆GTOTAL value than Ibuprofen (comparison drug).